2012
DOI: 10.1016/j.psychres.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the psychometric properties of the Internet Addiction Test (IAT) in US college students

Abstract: Internet addiction is a growing concern; however, both a clear understanding of the mechanisms driving problematic behaviors and a gold standard instrument for assessing symptoms are lacking. The purpose of this study was to perform a psychometric analysis of the most widely used screening instrument, the Young Internet Addiction Test (IAT), using a sample of US college students. 215 (70% response rate) undergraduate college students were recruited from two US universities to complete an online version of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
4
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(140 citation statements)
references
References 27 publications
(29 reference statements)
9
116
4
4
Order By: Relevance
“…On the whole, existing validation studies performed on the IAT showed a six-factor solution (Widyanto & McMurran, 2004), a three-factor solution (Chang & Law, 2008), a two-factor solution (Barke, Nyenhuis, & Kröner-Herwig, 2012;Faraci, Craparo, Messina, & Severino, 2013;Jelenchick, Becker, & Moreno, 2012;Korkeila, Kaarlas, Jääskeläinen, Vahlberg, & Taiminen, 2010;Watters, Keefer, Kloosterman, Summerfeldt, & Parker, 2013), or a one-factor solution (Faraci et al, 2013;Khazaal et al, 2008;Korkeila, Kaarlas, Jääskeläinen, Vahlberg, & Taiminen, 2010). The heterogeneity of these results can be attributed to the fact that many studies used this scale in various settings with a diversity of participants (e.g., different ages, nationalities; Faraci et al, 2013).…”
Section: The S-iat-sex: Validation and Links With Online Sexual Prefementioning
confidence: 99%
“…On the whole, existing validation studies performed on the IAT showed a six-factor solution (Widyanto & McMurran, 2004), a three-factor solution (Chang & Law, 2008), a two-factor solution (Barke, Nyenhuis, & Kröner-Herwig, 2012;Faraci, Craparo, Messina, & Severino, 2013;Jelenchick, Becker, & Moreno, 2012;Korkeila, Kaarlas, Jääskeläinen, Vahlberg, & Taiminen, 2010;Watters, Keefer, Kloosterman, Summerfeldt, & Parker, 2013), or a one-factor solution (Faraci et al, 2013;Khazaal et al, 2008;Korkeila, Kaarlas, Jääskeläinen, Vahlberg, & Taiminen, 2010). The heterogeneity of these results can be attributed to the fact that many studies used this scale in various settings with a diversity of participants (e.g., different ages, nationalities; Faraci et al, 2013).…”
Section: The S-iat-sex: Validation and Links With Online Sexual Prefementioning
confidence: 99%
“…However, the IAT was tested only for temporal reliability, using Pearson's correlation, and not for agreement (e.g. Jelenchick et al, 2012). Consequently, in the context of longitudinal studies aiming at evaluating the evolution of Internet addiction through time, a significant change in the IAT does not necessarily imply a real evolution of the respondents.…”
Section: Introductionmentioning
confidence: 99%
“…O Internet Addiction Test -IAT (Young, 1998 -traduzido e adaptado por Conti, et al, 2012) é considerado o primeiro instrumento para a avaliação da dependência de internet e encontra-se adaptado para diversos idiomas, incluindo o português (Conti, et al, 2012;Jelenchick, Megan, & Moreno, 2012;Widyanto & McMurran, 2004). É autoadministrado, formado por 20 itens, que medem a extensão do envolvimento com o computador e classifica a dependência em termos de prejuízo, incluindo o grau em que o uso da internet afeta a rotina diária, a vida social, a produtividade e o padrão de sono do indivíduo (Conti, et al, 2012;Young & Abreu, 2011;Widyanto & McMurran, 2004).…”
Section: Instrumentosunclassified